Increasing Teacher Competence Through Teacher Activity Centers in Group 1 Tajuk Reggali Central Aceh District - Suhara, Afni; Fitrah, Hariki; Khairani, Cut (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The realization of quality education cannot be separated from the role of teachers as professional educators. The aim of this research is to explore programs at the Teacher Activity Center in cluster 1 Tajuk Renggali, Silih Nara District. This research is a qualitative research. Data was collected through observation, interviews and documentation. The informants in this research consisted of the head of the teacher activity center, and teachers involved in Cluster 1 Tajuk Renggali. To ensure the validity of the data, triangulation techniques were used. Data analysis uses data reduction, data display and drawing conclusions. The research results show that there are several programs at the Tajuk Renggali Cluster 1 Activity Center, namely; a) program for making learning tools, designing methods, teaching aids and creating learning media, b) road to school program which is held once a month, and c) best class competition.